Living Hadith: The Role of Husband and Wife in Family Law - Moh. Hafid; Umi Sumbulah (LEGAL BRIEF, 2022)
In fostering a family, of course, husband and wife both have rights and obligations in playing their role. It's just that sometimes, each party does not fully understand each other's wars. So that what happens results in the erosion of the integrity of a family. This is more in the selfish attitudes that arise when problems occur. The husband proudly assumes that he has full power over his wife so that he must treat her badly. So the wife, sometimes always demands and blames her husband for not being able to provide all his needs and desires. Whereas in the words of the Messenger of Allah it is very clear that the husband has a role as a good leader, is responsible and must be understanding. His wife also as the leader must always obey and take care of household affairs as well as possible. This study uses library research with a living hadith approach. The results achieved are that there are four patterns of husband and wife roles: 1) Senior-Junior Partner pattern, 2) Equal Partner Relationship, 3) deliberation pattern and 4) maintenance and protection pattern.